Pengembangan Kawasan Wisata Kuliner di Kota Kolaka - Saleh Rabulan Makaffan; Andi Muhammad Akbar; Muhammad Zaki (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2023)
The COVID-19 pandemic has significantly altered the lifestyles of communities with mobility restrictions and Work From Home (WFH) mandates. This has led to increased levels of stress and monotony. As regulations gradually ease, people are seeking new activities. Culinary tourism has become a primary attraction in Indonesia, including Kota Kolaka, which holds significant potential as a culinary destination. However, this area faces architectural planning challenges, including inadequate supporting facilities, zoning ambiguity, and poor drainage systems. This study adopts a descriptive analysis method and a qualitative approach to collect data. The findings describe the characteristics of Kota Kolaka, including administrative conditions, topography, climate, demographics, and hydrology. The culinary tourism area in Kota Kolaka also requires thorough architectural planning, considering the local community's characteristics. An approach that blends traditional and modern elements, such as Neo Vernacular Architecture, is a suitable solution. The analytical results encompass solar orientation, site processing, and structural and sub-structural planning. With these steps, Kota Kolaka's culinary tourism area has the potential to become a sustainable tourist attraction, supporting local economic growth and promoting cultural heritage and regional cuisine. Special attention to environmental preservation and active community involvement in project implementation are necessary for achieving long-term sustainability